GC-MS Analysis of Rhus Tripartita Roots Extract (Journal of Humanitarian and Applied Sciences, 2023)
Rhus Tripartita is a rocky bush belongs to Anacardiaceae family, well known for uses in folk medicine in north Africa, and known locally in Libya with Jdari name. The ethanolic extract of dried roots powder was analyzed using GC-MS.  Sixty-three compounds were identified, which half of them are fatty acid esters, six long chain alcohols, three ketones, three long chain alkenes, two phytosterols, four heterocyclic compounds, four carboxylic acids, two acid chlorides and two sulfones. The major components of the extract were (9Z,12Z) Octadecadienoyl chloride, (9E,12E) Octadecadienoyl chloride, (E)-9-Octadecenoic acid methyl ester with peak percent of 46.89%, and Hexadecanoic acid methyl ester, 14-Methyl Pentadecanoic acid methyl ester with peak percent of 11.62 %. The extract of Rhus Tripartita is very rich with bioactive organic components which may explain the extensive usage in traditional medicine.
Keywords: Rhus Tripartita; GC analysis; Fatty acid esters; Bioactive compounds